Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{a}{\sqrt{b}-1}+\frac{b}{\sqrt{c}-1}+\frac{c}{\sqrt{c}-1}\ge\frac{\left(\sqrt{a}+\sqrt{b}+\sqrt{c}\right)^2}{\sqrt{a}+\sqrt{b}+\sqrt{c}-3}=\frac{t^2}{t-3}=12.,\)
\(t^2-12t+36=0\Leftrightarrow t=6;.\)
=>a =b =c = 4
Ta có:
\(\frac{2}{\sqrt{a}}+\frac{2}{\sqrt{b}}+\frac{2}{\sqrt{c}}=\left(\frac{1}{\sqrt{a}}+\frac{1}{\sqrt{b}}\right)+\left(\frac{1}{\sqrt{b}}+\frac{1}{\sqrt{c}}\right)+\left(\frac{1}{\sqrt{c}}+\frac{1}{\sqrt{a}}\right)\)
\(\ge\frac{\left(1+1\right)^2}{\sqrt{a}+\sqrt{b}}+\frac{\left(1+1\right)^2}{\sqrt{b}+\sqrt{c}}+\frac{\left(1+1\right)^2}{\sqrt{c}+\sqrt{a}}\)
\(=\frac{4}{\sqrt{a}+\sqrt{b}}+\frac{4}{\sqrt{b}+\sqrt{c}}+\frac{4}{\sqrt{c}+\sqrt{a}}\)
=> \(2\left(\frac{1}{\sqrt{a}}+\frac{1}{\sqrt{b}}+\frac{1}{\sqrt{c}}\right)\)\(\ge4\left(\frac{1}{\sqrt{a}+\sqrt{b}}+\frac{1}{\sqrt{b}+\sqrt{c}}+\frac{1}{\sqrt{c}+\sqrt{a}}\right)\)
=> \(\frac{1}{\sqrt{a}}+\frac{1}{\sqrt{b}}+\frac{1}{\sqrt{c}}\)\(\ge2\left(\frac{1}{\sqrt{a}+\sqrt{b}}+\frac{1}{\sqrt{b}+\sqrt{c}}+\frac{1}{\sqrt{c}+\sqrt{a}}\right)\)
"=" xảy ra <=> a =b =c.
Cho a>1,b>1,c>1. Chứng minh : \(\frac{a}{\sqrt{a-1}}+\frac{b}{\sqrt{b-1}}+\frac{c}{\sqrt{c-1}}\ge6\)
\(VT=\frac{a}{\sqrt{a-1}}+\frac{b}{\sqrt{b-1}}+\frac{c}{\sqrt{c-1}}=\frac{a-1+1}{\sqrt{a-1}}+\frac{b-1+1}{\sqrt{b-1}}+\frac{c-1+1}{\sqrt{c-1}}\)
\(VT\ge\frac{2\sqrt{a-1}}{\sqrt{a-1}}+\frac{2\sqrt{b-1}}{\sqrt{b-1}}+\frac{2\sqrt{c-1}}{\sqrt{c-1}}=6\) (đpcm)
Dấu "=" xảy ra khi \(a=b=c=2\)